Relationship between Students’ Self-Construal and Decision Making Styles at University Level - Altaf, Fasiha; Jabeen, Sadia; Younas, Sobia (Pakistan Languages and Humanities Review, 2022)
Present study aimed to investigate relationship between students’ self-construal and decision making styles at university level. Correlational research design was used to investigate the relationship between the variables. Population of the study was consisted on all university students in Lahore. Simple random sampling technique was used to select the sample. Sample of the study was 200 male and female students from public and private universities in Lahore. Self-construal scale and decision-making scale were used for data collection. Reliability of the instruments were .869 and .756 respectively. Findings of the study revealed that there was significant positive moderate correlation existed between students’ self-construal and decision-making styles at university level. Findings further concluded that there was significant mean difference existed between university students’ perceptions about self-construal and decision-making based on their gender, university type, qualification and age. There is an emerging group of students hold an interdependent self-construal. Therefore, findings of this study suggested that different decision-making styles should be used according to the students having different behavior to improve their performance and interpersonal relationships at university level.